What’s the Right Rite? Bonhoeffer, Climate, and Prayers of Confession (Tidsskrift for Praktisk Teologi, 2024)
In the face of ecological crises, we are largely still living in what Joanna Macy calls “Business as Usual,” even as global systems are shifting and irreversible tipping points nearing or already even past.  I explore here how, if at all, the practice of corporate confession empowers Christians to engage these questions, arguing that we need a much richer liturgical repertoire of practices.  I approach these questions through Dietrich Bonhoeffer’s resistance to “cheap grace” in relation to the tangle of structural sin, complicity, and inextricability involved in contemporary eco-justice questions and in relation to eco-anxiety and other eco-/climate emotions.  I use this lens to analyze forms of corporate confession from the Evangelical Lutheran Church in America’s liturgical resource Sundays & Seasons.  In the conclusion, I point to larger forms of practice that could complement confession and help restore it to its proper role in fostering costly grace.